1992
DOI: 10.1111/j.1365-2125.1992.tb03996.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of varying doses of aspirin on human platelet activation induced by PAF, collagen and arachidonic acid.

Abstract: 1. The effect of increasing doses of orally administered aspirin (30‐ 900 mg) on platelet aggregation and ATP release induced by arachidonic acid (AA), collagen and platelet activating factor (PAF) was assessed in 12 normal volunteers. 2. Aspirin ingestion was associated with a significant increase in EC50 for AA (P less than 0.0001) and collagen (P less than 0.0001) but not for PAF (P greater than 0.495) although the normal biphasic aggregation response for the latter was abolished. Maximum ATP release was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 29 publications
2
21
1
Order By: Relevance
“…TXA 2 receptor antagonism did not influence PAF‐induced platelet P‐selectin expression in the present study, whilst TXA 2 synthesis blockade by aspirin has previously been shown to inhibit PAF‐induced platelet aggregation [25]. Our results suggest that PAF‐induced platelet TXA 2 synthesis may be limited in unstirred hirudinized blood, as both physiological calcium levels and the lack of cell–cell contact may limit platelet TXA 2 synthesis [26].…”
Section: Discussioncontrasting
confidence: 48%
“…TXA 2 receptor antagonism did not influence PAF‐induced platelet P‐selectin expression in the present study, whilst TXA 2 synthesis blockade by aspirin has previously been shown to inhibit PAF‐induced platelet aggregation [25]. Our results suggest that PAF‐induced platelet TXA 2 synthesis may be limited in unstirred hirudinized blood, as both physiological calcium levels and the lack of cell–cell contact may limit platelet TXA 2 synthesis [26].…”
Section: Discussioncontrasting
confidence: 48%
“…Several research groups have begun evaluating the effect of ASA in combination with other drugs (8, 12, 13, 4449). Nonetheless, the effectiveness of such combined therapeutic approaches after exposure to defined dynamic shear stress profiles has been poorly studied and defined.…”
Section: Discussionmentioning
confidence: 99%
“…ATP secretion was determined in parallel to platelet aggregation in aliquots of 0.45 mL PRP along with 50 µL of luciferin/luciferase (to measure ATP secretion, Chrono‐lume reagent, Chronolog, Corp.), in a platelet aggregometer (model 560, Chronolog Corp.) at 37 °C, with continuous stirring at 1200 r.p.m. [18].…”
Section: Secretion Studiesmentioning
confidence: 99%